A 25 year single centre experience in 128 patients with primary sclerosing cholangitis. (13th March 2011) - Chapman, M H; Bannoo, S; Webster, G; Johnson, G; Hatfield, A R; Pereria, S P; Johnson, G
Abstract : Introduction: Dominant biliary strictures (DS) occur commonly in patients with primary sclerosing cholangitis (PSC), who have an increased risk of developing cholangiocarcinoma (CCA). The natural history and optimal management of dominant strictures remains controversial with most reports suggesting that endoscopic interventions improve outcome. Methods: The authors describe a 25 year experience of endoscopic retrograde cholangiopancreatography (ERCP) in patients with PSC at a single tertiary referral centre in London. Patients were identified through case note review, endoscopy and pathology database searches and through a specific PSC database. Results: During a mean follow-up of 6 years (0.1–23.6 years), 128 patients with PSC (81 M, 47 F; median age 49 years) had a median of 2 ERCPs (range 1–24). 70 patients with dominant biliary strictures had a median of 3 (range 0–34) interventions, compared to 1 (0–7) in the 58 without dominant strictures. Endoscopic interventions included: (1) stenting alone (51%), (2) dilatation alone (19%) or (3) dilatation and stenting (16%), while 14% had no or failed interventions, most of whom required percutaneous transhepatic drainage. There were no procedure-related deaths. The survival of those with dominant strictures was worse than those without, even after exclusion of those who developed CCA. Use of ursodeoxycholic acid was not significantly different between groups. CCA developed in 20/128 patients (16%), only in those with dominant strictures (20 of 70, 29%, compared to 0 of 58). Jaundice was the presenting feature in 15 (75%) of those with CCA, which developed a median of 3 years (0–21 years) after the diagnosis of PSC, with 8/20 (40%) presenting within the first year. Mean time from diagnosis of CCA to death was 7 months (1–23 months). Conclusion: Repeated endoscopic therapy in patients with PSC appears to be safe. However, this data highlights the poor prognosis in the subgroup with dominant strictures, even after exclusion of those who developed CCA. In this series, CCA only occurred in patients with dominant bile duct strictures.